Electronically induced modification of thin layers on surfaces - Bauer, U.; Neppl, S.; Menze, D.; Feulner, P.; Shaporenko, A.; Zharnikov, M. (Физика низких температур, 2007)
Interactions of thermally and electronically stimulated reactions in thin layers on surfaces are investigated.
For self-assembled monolayers, thermal activation promotes many processes primarily induced by
electronic excitations. We demonstrate that the film temperature is an important parameter for steering these
reactions towards different final products. Using chemisorbed water on Ru(001) as an example, we investigate
how the products of an irradiation induced reaction catalyze thermally stimulated dissociation of water
molecules.